TESTING OF CONSTRUCTION MATERIALS FOR CAVITATION RESISTANCE - Tarasenko, Taras; Badakh, Valery; Makarenko, Mykola; Dubkovetsky, Ihor (Problems of Friction and Wear, 2024)
The article presents the results of experimental studies of the cavitation erosion of structural materials widely used in aviation hydraulic drives. The effect of the air saturation of the working fluid on the intensity of the cavitation erosion of structural materials was determined. It is proposed to use as a cavitation generator a throttle device functioning in the mode of developed cavitation when investigating the cavitation resistance of structural materials. The effectiveness of throttle cavitation generators was evaluated based on their flow-difference characteristics. The design of the cavitation chamber for testing structural materials for cavitation resistance is presented. A mechanism of cavitation erosion is proposed, in which the mechanical influence of shock waves and microjets on the surface of the test sample dominates. The incubation period of structural materials that are widely used in hydraulic engineering and their cavitation resistance are determined. The rate of cavitation erosion caused by the supply pressure on the cavitation generator was studied. It was determined that the cavitation erosion of plastic materials occurs almost linearly, while for solid materials the nonlinear dependence is observed. It is proposed to increase the fatigue life of structural materials, which are widely used in aircraft construction, by cavitation treatment of their surface within the incubation period of the cavitation.